Cancer Prevention in Patients with GERD and Barrett's Esophagus: Surgery. Issue 1 (March 2021) - Oelschlager, Brant K.; Carrera Ceron, Rocio E.
Barrett's esophagus (BE) is an acquired pre-malignant condition that is the result of chronic damage to the esophagus mucosa caused by reflux. Gastroesophageal reflux disease (GERD) and BE are major risks factors for esophageal adenocarcinoma. Effective treatment for BE should control GERD symptoms but these patients frequently presents with other associated conditions that makes management more challenging. Laparoscopic antireflux surgery (LARS), restoring the gastroesophageal barrier, is a very effective treatment of patients with BE, but its role in cancer prevention remain controversial. There is strong evidence that surgery can promote regression, but less so for reducing progression. The aim of this article was to review the current role of antireflux surgery in preventing progression to dysplasia or cancer in patients with BE and GERD.